ARDEREA EMOŢIONALĂ LA PROFESORII UNIVERSITARI - USM ADMIN (Moldova State University, 2009)
The main objective of this paper is to explore the phenomenon of burnout syndrome to university teachers in Moldova. We were interested to clarify also the relations between burnout syndrome, gender and age. The empirical research was based on Maslach Burnout Inventory, developed by Cristina Maslach. The results confirm the hypothesis proposal in this research.